Ursolic and oleanolic acids: two natural triterpenoids targeting antibacterial multidrug tolerance and biofilm formation - Spaggiari, Chiara; Annunziato, Giannamaria; Costantino, Gabriele (Frontiers in Natural Products, 2024)
Natural products have been used since ancient times to treat various ailments and have been recognized for many years as a source of therapeutic agents and structural diversity. Plant-derived products have thus served as dietary components but also to maintain a state of wellbeing and health by preventing different diseases both of inflammatory and infective nature. Pentacyclic triterpenoids, particularly ursolic acid (UA) and oleanolic acid (OA), are well-studied natural products endowed with complex biological profiles. In this mini-review, we summarized the most advanced results on extraction methodologies and antimicrobial activity of UA and OA, focusing on their potential role as antimicrobic adjuvants, bacterial biofilm inhibitors and related mechanisms of action. This offers a theoretical basis and inspiration for further studies on their bioactivity mechanism.